Odontolabis pareoxa vietnamensis Yamamoto & Pham, a new subspecies of stag beetle (Coleoptera: Lucanidae) from northern Vietnam - Yamamoto, Shûhei; Pham, Phu Van (Zootaxa, 2025)
The stag beetle genus Odontolabis Hope, 1842 (Lucanidae: Odontolabini) contains approximately 60 species, predominantly restricted to the Oriental Region, with 6 named species from Vietnam. Here, we describe a new subspecies of Odontolabis pareoxa Bomans, Lacroix & Ratti, 1973 from Yên Bái Province in northern Vietnam: Odontolabis pareoxa vietnamensis Yamamoto & Pham, new subspecies. This new subspecies is distinguishable from the nominotypical subspecies by cephalic and pronotal characteristics in males. The findings also indicate a partial similarity in the stag beetle fauna between northern Vietnam and adjacent areas of northern Myanmar.